MATHEMATICAL MODELS AND ALGORITHMS OF CRYPTOGRAPHIC DATA PROTECTION IN DISTRIBUTED INFORMATION SYSTEMS - Pasichnyk, V. A.; Pasichnyk, A. N.; Riabenko, V. I. (Systems and Technologies, 2026)
In modern conditions, information networks and data processing and transmission centers are a determining factor in the effective functioning of management systems of state institutions, financial and industrial organizations, energy and communications enterprises, transport and logistics infrastructure. Accordingly, the increase in the number of such centers and the number of different communication lines between them significantly increases the risks of unauthorized access to confidential information, ensuring data security and integrity. Therefore, the study of the problem of information security is of great importance for preventing and countering phishing attacks, which are constantly exposed to both individual enterprise networks and national networks. The paper analyzes mathematical models that describe the process of information protection using cryptographic data encryption algorithms. The practical application of the algorithms of the given substitution, the Vigenère cipher, and selfsynchronizing stream ciphers is considered. To increase the stability of the ciphertext, a modification of the Vigenère algorithm is proposed using separate unified alphabet tables for the text and the encryption/decryption key. Recommendations are developed for the use of the considered crypto algorithms to ensure effective protection of information systems from intentional or accidental interference. To increase the efficiency of the use of crypto algorithms, the feasibility of the integrated use of symmetric and asymmetric encryption methods to use their positive qualities, such as the speed of processing secret keys and the security of their transmission, is indicated. Promising directions for the development of information security systems using cryptographic algorithms are identified.